Market Reaction on The Announcement of SRI-KEHATI and FTSE4GBM Indices - Lydia Ivana Kumajas; Sri Murni; Maryam Mangantar; Ivonne Stanley Saerang; Joy Elly Tulung (AIBPM Publisher, 2022)
This study aims to determine the market reaction to the announcement of additional shares on the SRI-KEHATI and FTSE4Good (F4GBM) Index during the Covid 19 2020 and 2021 periods. The indicator of market reaction is observed through Trading Volume Activity (TVA). The results show that there is a significant TVA around the announcement date on both observed indices, this study uses an event study